Antidiscrimination Laws, Policy Knowledge and Political Support - Conrad Ziller; Marc Helbling (British Journal of Political Science, 2019)
This study investigates how antidiscrimination policy and related policy knowledge influence citizens' support for the democratic system and its institutions. The article argues that antidiscrimination measures and knowledge about rights to equal treatment foster perceptions of government responsiveness, which increase political support among target groups and citizens who advocate egalitarianism. Utilizing a longitudinal design and more valid measures to resolve causality issues, the results of the empirical models show that increases in policy knowledge over time systematically predict higher political support, especially among individuals who hold egalitarian values. Individuals who are discriminated against express particularly high political support in contexts where antidiscrimination laws are expanded. Overall, the results amplify the role of policy knowledge as a key factor in studying policy feedback effects.
doi:10.7910/DVN/MG11FA
Keywords: 330; antidiscrimination policy; policy knowledge; discrimination; policy effects; policy feedback; political support